Prospective Assessment of mrTRG System Used for Determining the Efficiency of Neoadjuvant Chemoradiotherapy in Patients with Rectal Cancer - T. P. Berezovskaia; Ya. A. Dayneko; A. A. Nevolskikh; S. A. Ivanov; A. D. Kaprin (Вестник рентгенологии и радиологии, 2021)
Background. Evaluation of the therapeutic effect of neoadjuvant chemoradiotherapy (nCRT) for rectal cancer (RC) is of prognostic value and allows to individually plan the type and extent of further surgical intervention. One of the most promising methods of MRI evaluation is magnetic resonance tumour regression grade (mrTRG) system. However, the reliability and safety of this method must be confirmed by the results of clinical trials and practical application.Objective: to analyze our experience in the prospective use of mrTRG system and evaluate the additional contribution of diffusion-weighted images (DWI) to its diagnostic efficiency.Material and methods. The mrTRG values were determined in 125 (including 30 with DWI) patients with locally advanced RC who received combined treatment with nCRT in Tsyb Medical Radiological Research Centre from 2015 to 2019. The obtained data were compared with the modified pathologic response based on Lushnikov’s definition, and the diagnostic parameters of differentiation of patients responding and nonresponding to nCRT were calculated.Results. When the mrTRG system was used without DWI, the following sensitivity and specificity values as well as positive and negative predictive values were obtained: 75%, 60%, 70% and 67%, respectively, with DWI – 87%, 87%, 87% and 87%, respectively.Conclusion. A prospective evaluation of the result of nCRT using the mrTRG system has moderate accuracy for stratification of patients responding and non-responding to nCRT, which requires the use of additional criteria for MRI scores to select patients who may receive less aggressive surgical treatment. Despite the small number of patients with DWI, we obtained higher values of the diagnostic parameters. In this regard, we consider it appropriate to use DWI when assessing the treatment response.